Trends, Challenges, and Benefits of the Flipped Classroom Model in EFL Context: A Systematic Literature Review - Hairuddin, Nurul Hidjrah; HALIM, Shanty; SAHRIANA, Sitti; IRMAWATI, Irmawati (Research and Innovation in Applied Linguistics, 2025)
This research aims to do a thorough evaluation and analysis of the trends, challenges, and benefits of Flipped Learning (FL) instruction within the English as a Foreign Language (EFL) setting. Instructional techniques in the EFL environment have been attempting to transition from a teacher-centered approach to a student-centered one. Emerging technology has enabled EFL educators to contemplate the FC model to achieve their educational aims. This study seeks to examine the current literature on the FL approach within the EFL setting and offers instructional recommendations for EFL trainers. This report synthesizes global quantitative and qualitative studies on flipped learning within the EFL context. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) is utilized for selection, screening, and reporting objectives. This study investigated chosen articles published throughout the last ten years (2014-2024), culminating in the inclusion of 88 articles for comprehensive analytical examination. There has been a heightened prevalence of flipped learning in the EFL context since 2020. The analysis indicated that the majority of studies on Flipped Learning within the EFL environment concentrated on students' language competencies, engagement, and academic performance. To enhance the evidence base and facilitate wider, context-aware adoption, future research should explore under-explored domains, diversify methodologies (particularly longitudinal and comprehensive qualitative designs).